The Role of Clinical Psychologist: Building a Comprehensive Understanding of 2e Students. (October 2015) - Amend, Edward R.; Peters, Dan
As clinical psychologists, our role is to provide psychological and educational testing, and counseling for children and their families. Our job is to understand the developmental trajectories and expectations across areas of functioning (i.e., behavior, self-regulation, cognitive, academic, and social), differentiate typical versus atypical development, and provide recommendations for accommodation, intervention, and growth in the home, at school, and in the community. As psychologists who work primarily with gifted and talented individuals, we see many with profound strengths as well as disabilities who are not easily categorized. These are twice-exceptional students. With twice-exceptionality, the diagnostic category, although important, is not the ultimate focus—identifying the needs and the strengths is equally, if not more, important.